Root Growth, Water and Nitrogen Use Efficiencies in Winter Wheat Under Different Irrigation and Nitrogen Regimes in North China Plain - Liu, Weixing; Wang, Jiarui; Wang, Chenyang; Ma, Geng; Wei, Qiongru; Lu, Hongfang; Xie, Yingxin; Ma, Dongyun; Kang, Guozhang (Frontiers in Plant Science, 2018)
Excessive nitrogen (N) application combined with water shortage has a negative effect on crop production, particularly wheat (Triticum aestivum L.) production in the North China Plain. This study examined root growth and water–nitrogen use efficiency in wheat grown on loam soil in the North China Plain, from 2012-2014 using a fixed–position experiment initiated in 2010. The experiment followed a completely randomized split–plot design with four replications, taking irrigation (no irrigation (W0) versus irrigation at jointing plus flowering (W2)) as the main plot and N treatment (0, 180, 240 and 300 kg N ha−1) as the subplot. Compared with W0, W2 increased grain yield and root weight density (RWD) by up to 91.3 and 57.7 % in 2012–2013, and 15.5 and 43.0 % in 2013–2014, respectively, across all N application rates. Irrigation had no effect on grain water-use efficiency (WUEY), but caused a decrease in biomass WUE (WUEF, WUEM and WUEDM). Significant improvements in grain yield and biomass WUE during vegetative growth stage, and reductions in nitrogen-use efficiency (NUE) and RWD, were observed with increasing N application. Compared with non-N treatment, N treatment increased yield by up to 98.9 and 93.7 % in 2012–2013 and 2013–2014, respectively, decreasing RWD by 12.0 and 16.9 %. Correlation analysis further revealed that RWD was positively correlated with grain yield, evapotranspiration (ET) and NUE. NUE was also positively correlated with nitrogen uptake efficiency (UPE). Overall, the findings suggest that optimal N application improves NUE by increasing above-ground nitrogen uptake (AGN) as a result of optimized RWD and a synchronous increase in WUE, thus increasing yield. Under the experimental conditions, an N application rate of 240 kg N ha–1 plus irrigation at jointing and flowering is recommended.